The The Influence of AI Awareness Dimension on Sustainable Employability: Study from Gen X Employees in Jakarta - Emilisa, Netania; Muna, Sarah Rizkika Ifa; Lukito, Nico; Wahyuni, Lidia; Apriani, Dietce (Humanitas: Indonesian Psychological Journal, 2024)
This study aimed to analyze the influence of the AI awareness dimension, namely challenge and hindrance appraisal toward AI, on sustainable employability through job crafting mediation variables in Gen X employees in Jakarta. In this study, hypothesis testing and data collection were carried out cross-sectionally. The data were collected primarily by distributing questionnaires to 272 Gen X employees in Jakarta. The sample collection method used the purposive sampling method. The data processing techniques included validity tests, reliability tests, and structural equation modeling (SEM). The results of the study showed that there was a positive influence caused by challenge appraisal toward AI and job crafting on sustainable employability. Meanwhile, hindrance appraisal toward AI triggered a negative influence on sustainable employability. The company and employees were expected to collaborate in implementing AI in the work environment to support their work sustainably.